Colombian Labor Monitors - Labor Monitor, Colombian; Korman, Hyman (La Sociología en sus Escenarios, 2009)
Abstract. The rebel conflict in Colombia is escalating, as insurgents have responded with some of their heaviest resistance to date to the U.S.-supported Plan Colombia counter-drug offensive. U.S. military and civilian personnel have become a primary target for the increasingly aggressive guerrillas, who have threatened retaliation against the United States inside and outside Colombia. The United States, the largest supporter of Colombia's war on drugs, has sought to avoid getting dragged into the country's civil war, making a clear distinction between counternarcotics and counter-insurgency operations. Part of this distinction includes limiting the number of U.S. military personnel and contractors operating in Colombia to 500 and 300 respectively. Resumen. La Guerra interna en Colombia se ha agudizado a partir de la implantación del Plan Colombia - una estrategia contrainsurgente y contra del narcotráfico. Personal militar y civil norteamericano se ha convertido en blanco de la guerrilla. USA, el mayor soporte en la guerra contra el narcotráfico y la guerrilla en Colombia políticamente distingue entre la guerra al narcotráfico y la contrainsurgencia. Plantea que esta ultima no es su prioridad limitando su presencia en 500 y 300 hombres respectivamente.